Elaboration of fish meal of fish (HPV) mojarra roja (oreochromis sp) and determination of its nutritional composition, as a food source for animals in Garzón (Huila). - Embus-Clavijo, Nelson
The objective of this work was to determine the nutritional composition of the red mojarra viscera (Oreocrhomis sp), making flour from it, for use in animal feed and as an alternative to mitigate the environmental impact that this product exerts. The viscera resulting from the benefit of the red mojarra, were cooked to obtain fish oil; The yield in viscera was 10.33%, with variations between 8 - 12% in this species; Of this viscera was obtained 30.32% in oil and 69.67% of solid residue cooked, with a humidity of 82.5%, which dropped to 72% when letting it drain for 3.5 hours; The sample was then dried in an oven with a hot air centrifugal fan, then ground in a hammer mill and sent to the laboratory, which reported the following HVP composition: Moisture 14.9%, Dry Matter 85.1% , Crude protein 48.7%, ethereal extract 40.3%, ash 12%, crude fiber 2.4% and macro and micro mineral elements. This composition shows a great nutritional value for animal feed. In the second phase of this work, the SENA will carry out the investigation of the inclusion in the diet for pigs.